Մարգարիտ Բաբայանի գործունեության թիֆլիսյան շրջանը - Նիկոլայ Կոստանդյան (ՀՀ ԳԱԱ հրատ.)
Статья посвящена тифлисскому периоду деятельности пианистки, певицы (меццо-сопрано), музыковеда и педагога Маргарит Бабаян (1874-1968), который длился до 1904 и развивался в трех направлениях.This article is about the Tiflis time period of activity of Margarit Babayan (1874-1968), who was a pianist, singer (mezzo-soprano), musicologist and pedagogue. This period lasted till 1904 and included three directions.
Keywords: Music